A visão dos jovens do Centro Federal de Educação Tecnológica de Mato Grosso sobre o consumo de drogas ilícitas - Sanches, Maria Ubaldina Costa (2005)
The question of the young thought, their practice comprehension and their vision about the use of illicit drugs need special attention. There are few experiences which consider the young as expressive interlocutors in the investigations, which aim at knowing how they live and face their lives, considering their experiences and attitudes about the use of drugs. The informations about the use of drugs in CEFET-MT community is very insufficient; there is a lack of projects and effective actions in the treatment of the questions related to the topic. This research aimed to characterize the young students of CEFET- MT and know their vision their about the use of illegal drugs. Participated in this research the students of High School, and the Chemical and Predial Constructions Courses of the Professional Education, trying to identify the points in common and not about the topic. The CEFET-MT community is composed mainly by B and C social economic classes. The most part of the students are single, live with their family and turn to them when in serious needs. They have a religion and like to go out with friends. They also aspire a good career. The majority of the youngs do not use illegal drugs. It was found that a few students specially the ones from Chemical Course make use of illegal drugs. Most of the students understand that the use of drugs is a problem and that the responsibility by this use and its consequences is of the users. Only a small number of investigated students think that the use of hemp should be legalized. Those that do not make use of illegal drugs have an intolerant attitude towards the people who uses it, but they have a different attitude when consider the use of drugs in a general way. It is possible to conclude that the young students have critical position regarding to social problems, they always wanting to take part in discussions and actions about them. This research was developed taking quality and quantity criterions basis. Questionnaires without personal identification andwith opened and closed questions where uses, and also groups interviews where used as methodological strategies. The data collection provided social, economic and family outline of the students of CEFET-MT, as well as information about their knowledge, opinions and use of drugs and also contemporary questions too.